2023
DOI: 10.1002/jcc.27099
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of probe rheology simulation technique in atomistically detailed molecular dynamics simulations

Abstract: The probe rheology simulation technique is a technique for measuring the viscosity of a fluid by measuring the motion of an inserted probe particle. This approach has the benefit of greater potential accuracy at a lower computational cost than other conventional simulation techniques used for the calculation of mechanical properties, such as the Green–Kubo approach and nonequilibrium molecular dynamics simulations, and the potential to allow for sampling local variations of properties. This approach is impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…39 The breakdown of Stokes' law may be attributed to the increase of fluid viscosity in the vicinity of the particles 40 or a failure of the continuum approximation. 41 Besides the stick boundary conditions, slip boundary conditions have also received extensive attention. [42][43][44] It has been indicated that smooth particles follow Stokes' law with slip boundary conditions, whereas the stick boundary conditions are valid for rough particles.…”
Section: Introductionmentioning
confidence: 99%
“…39 The breakdown of Stokes' law may be attributed to the increase of fluid viscosity in the vicinity of the particles 40 or a failure of the continuum approximation. 41 Besides the stick boundary conditions, slip boundary conditions have also received extensive attention. [42][43][44] It has been indicated that smooth particles follow Stokes' law with slip boundary conditions, whereas the stick boundary conditions are valid for rough particles.…”
Section: Introductionmentioning
confidence: 99%